Health-related quality of life, participation, and physical and cognitive function of patients with intensive care unit-acquired muscle weakness 1 year after rehabilitation in Germany: the GymNAST cohort study. Issue 7 (13th July 2018) - Thomas, Simone; Mehrholz, Jan
Abstract : Objective: To describe predictors for health-related quality of life, participation, physical activity and cognitive function in patients with intensive care unit (ICU)-acquired muscle weakness 1 year after discharge from rehabilitation. Design: This is a cohort study. Participants: We included 150 chronic critically ill individuals with ICU-acquired muscle weakness. Setting: Postacute ICU and rehabilitation units in Germany. Measures: We measured health-related quality of life using the EQ-5D, participation using the Reintegration of Normal Living Index, physical activity using the Physical Activity Scale for Individuals With Physical Disabilities, and basal cognitive function using the Montreal Cognitive Assessment (MoCA) at 6 months, and the Clock Drawing Test 6 and 12 months after discharge from postacute treatment. We described the predictors of the results at 12 months. Results: The best predictors for good health-related quality of life 1 year after discharge were the time until regaining walking ability (OR=0.96, OR per day, 95% CI 0.93 to 0.99) and the mean MoCA score on admission to our postacute ICU and rehabilitation units (OR=1.25, 95% CI 1.02 to 1.52).The best predictor for good participation 1 year after discharge was the MoCA sum score on admission to our postacute ICU and rehabilitation units (OR=0.85, 95% CI 0.72 to 1.00). The best predictor for good physical activity 1 year after discharge was the Apache sum score on admission to our postacute ICU and rehabilitation units (OR=1.68, 95% CI 0.89 to 3.13). The best predictor for normal cognitive function 1 year after discharge was regaining walking function in rehabilitation (OR=8.0, 95% CI 0.49 to 13.69). Conclusion: Recovery of health-related quality of life, participation, physical activity and basal cognitive function was still not complete 12 months after discharge from postacute treatment. We described the predictors for these important outcomes in participants with ICU-acquired muscle weakness 1 year after discharge from rehabilitation. Trial registration number: DRKS00007181.